The Impact Of Extreme Summer Melt on Net Accumulation of an Avalanche Fed Glacier, as Determined by Ground‐Penetrating Radar. Issue 4 (December 2015) - Purdie, Heather; Rack, Wolfgang; Anderson, Brian; Kerr, Tim; Chinn, Trevor; Owens, Ian; Linton, Matthew
ABSTRACT: Glacier mass balance is more sensitive to warming than cooling, but feedbacks related to the exposure of previously buried firn and ice in very warm years is not generally considered in sensitivity studies. A ground‐penetrating radar survey in the accumulation area of Rolleston Glacier, New Zealand shows that five years of previous net accumulation was removed by melt from parts of the glacier above the long‐term equilibrium line altitude during a single negative mass balance year. Rolleston Glacier receives a large amount of accumulation from snow avalanches, which may temporarily buffer it from climate warming by providing additional mass that has accumulated at higher elevations, effectively increasing the elevation range of the glacier. However, glaciers reliant on avalanche input may have high sensitivity to climatic variations because the extra mass is concentrated on a small part of the glacier, and small variations in avalanche input could have a large impact on overall glacier accumulation. Further research is needed to better estimate the amount and spatial distribution of accumulation by avalanche in order to quantify the climate sensitivity of small avalanche‐fed glaciers.